TERRITORIAL DYNAMICS AND MULTIMODAL LEARNING IN BOARDING HOUSES: AN EXPLORATION OF ARCHITECTURE STUDENTS EXPERIENCES - Narida, Tisya Surya; Setijanti, Purwanita; Cahyadini, Sarah (Border: Jurnal Arsitektur, 2025)
Among the various types of residences, the boarding house stands out as a distinctive temporary home, acting as a surrogate environment for individuals who are far from their permanent homes. Beyond serving as a place of shelter, it supports the continuity of daily life by offering spaces for rest, study, and social interaction. This is particularly significant in architectural education, where learning involves multimodal methods: visual, aural, read/write, and kinesthetic. These learning styles are deeply embedded in studio-based practices like model-making. However, a research gap exists in understanding how architecture students’ study activities influence spatial dynamics and territoriality in shared boarding house environments. To explore this, a multi-method approach was used, including traffic lane observations, interviews, and image documentation. Findings revealed two types of territorial infringement: one caused by academic activities such as design work and model-making, and another involving contamination and minor spatial violations during detailed model production. These infringements stem from shared ownership, limited space, and the nature of architectural tasks. The study suggests two architectural design strategies to mitigate these issues: incorporating fixed features to define zones clearly and providing semi-fixed features to accommodate changes in use. These solutions aim to balance communal living with individual academic needs.